Agricultural commodity projections, 1970-1980 : volume II: part I, general methodology; part II, statistical appendix - Food and Agriculture Organization of the United Nations (Rome, 1971)
The present volume contains a description of the methodological approach used in the projection study and a statistical appendix of background table
Vol. II
Includes bibliographical references.
osc 02/08/2019
Loans
Keywords: Produce trade; Produce trade